2022
DOI: 10.32479/ijeep.11956
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Energy to Drive Renewable Energy Diversity in Bibliometric Analysis

Abstract: Hybrid energy is a combination of two or more energy sources, some of which can be sourced from several renewable energies combined, or combined with fossil energy. Renewable energy diversity is implemented through the development of hybrid energy in order to obtain new energy sources that are more effective and efficient. Bibliometric analysis is directed to analyze topics that have novelty according to the time period of publication based on qualitative methods. Analysis of scientific literature sourced from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The data analysis carried out in this research is sourced from Google Scholar, which utilizes a database of scientific journals related to economic recovery, displayed in the form of network visualization and density using the VOSviewer application. The visualization presented by VOSviewer is displayed attractively and elegantly (Sarjana et al, 2022), shown in the form of visually informed mapping (Abdullah et al, 2020), and the results of the analysis are presented in an attractive visualization (Sarjana et al, 2021). Scientific journal specifications refer to scientific evolution resulting from the disclosure of various theories and topics raised to discover the trends that most often appear for research and those that are still relatively rarely studied so that they can be developed in future research.…”
Section: Methodsmentioning
confidence: 99%
“…The data analysis carried out in this research is sourced from Google Scholar, which utilizes a database of scientific journals related to economic recovery, displayed in the form of network visualization and density using the VOSviewer application. The visualization presented by VOSviewer is displayed attractively and elegantly (Sarjana et al, 2022), shown in the form of visually informed mapping (Abdullah et al, 2020), and the results of the analysis are presented in an attractive visualization (Sarjana et al, 2021). Scientific journal specifications refer to scientific evolution resulting from the disclosure of various theories and topics raised to discover the trends that most often appear for research and those that are still relatively rarely studied so that they can be developed in future research.…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge mapping is applied to develop various required study topics according to the level of urgency [48]. Qualitative research is applied in this study through a review of scientific literature originating from journal publications [49]. Research analysis uses bibliometric analysis that examines various scientific literatures as main data source [50].…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the findings of each period can be presented referring to the categorization of data collected so that the progress of each publication period can be known. Issues that have novelty that refer to developmental patterns in scientific evolution can be used as new studies to strengthen knowledge development and support sustainable development [49][56] [57].…”
Section: Methodsmentioning
confidence: 99%